Pemanfaatan Media dan Upaya Peningkatan Kualitas Hasil Belajar - Sri Putrianingsih (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
Learning and learning are interrelated things, we can even interpret them as two activities that have important wars in human life. Learning without learning is not necessarily producing a desired learning goal, so it is important to have learning. Learning is an activity that can be done in formal institutions and non-formal institutions. The development of science in the world of education and also in modern times determines to have a major influence on the development of learning. In 2002, learning enough with the media and simple methods used by the teacher, the target was students to understand the lesson and students can learn from the books they had learned. But nowadays the learning process is not enough with media and simple methods, given the importance of media innovation - the media used in learning, with the aim that students can understand the material delivered by educators and the learning process is more enjoyable. Every student learning effort, especially parents also hopes that my child is able to master the subject matter they have learned, both at home and at the tutoring site. Teachers and parents can monitor the learning performance of students or children through learning outcomes, which we usually know as "report cards". Report cards show, explain children's learning activities while in formal institutions or schools, through report cards people know to know the increase in their child's learning outcomes. Understanding the subject matter, even passively learning in certain subjects, which can be used as motivation for educators and parents, so that in the future subject matter that has not been active can be evaluated by educators and teachers so that they can improve their learning. The use of the media used by these educators places great hope on students so that they can understand, understand and apply the subject matter to the maximum, through creative media educators hope that the learning outcomes will increase.